2008
DOI: 10.1111/j.1095-8312.2007.00896.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological aspects and phylogenetic analyses of pollination systems in the Tylophora-Vincetoxicum complex (Apocynaceae-Asclepiadoideae) in Japan

Abstract: Pollinators of two Cynanchum, five Tylophora, and 16 Vincetoxicum species were observed in 26 populations in Japan. The following pollination systems were observed in 18 species: moth pollination, generalized insect pollination, wasp pollination, dipteran pollination, both dipteran and moth pollination, and autogamy. Principal component analysis based on 13 floral characters indicated that the size of the pollinator tended to increase with sizes of all characters measured. Furthermore, species that have develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
42
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 25 publications
0
42
0
1
Order By: Relevance
“…As noted earlier (Yamashiro & al., 2004a), the taxa of clade E show very little genetic diversity in all regions studied. On the other hand, Yamashiro & al. (2008) showed that floral characters in this clade are highly diverse, as are the pollination systems.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As noted earlier (Yamashiro & al., 2004a), the taxa of clade E show very little genetic diversity in all regions studied. On the other hand, Yamashiro & al. (2008) showed that floral characters in this clade are highly diverse, as are the pollination systems.…”
Section: Discussionmentioning
confidence: 99%
“…The four European species (V. creticum, V. hirundinaria, V. nigrum, V. rossicum) form a very well supported subclade (F321) in sister-group position to an also well-supported subclade comprising four erect species of temperate Asia (F322). Yamashiro & al. (2008) noted that the flowers in their clade I, which corresponds to clade F32 of the present analysis, comprises many taxa not producing nectar and having small and inconspicuous flowers.…”
Section: Pentatropis Madagascariensis (7)mentioning
confidence: 99%
See 2 more Smart Citations
“…Specifi cally, a better understanding of the order of evolution and the lability of individual traits and of the patterns of correlated evolution among those traits could greatly enhance our understanding of the processes that may have led to current variation in fl oral morphologies ( P é rez et al, 2006 ). Some studies have addressed the patterns of evolution of individual fl oral traits that are associated with attractiveness to animals (reviewed by Fenster et al, 2004 ; with subsequent studies by Ackermann and Weigend, 2006 ;P é rez et al, 2006, Whittall and Hodges, 2007Okuyama et al, 2008 ;Smith et al, 2008 ;Tripp and Manos, 2008 ;Yamashiro et al, 2008 ). However, no study has ever evaluated the exact order of evolution of individual traits in a temporal context.…”
Section: Methodsmentioning
confidence: 99%